Digital Payment, E-Commerce, and Social Media Effects on Halal Culinary Purchase Decisions: Evidence from Yogyakarta, Indonesia - Ifa Azzahra Farhatannisa; Miftahus Surur (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The development of science and technology in the food sector enables food or beverage production to be carried out quickly and efficiently. One aspect that has received attention is the need for halal food or drinks. The concept of